PENERAPAN PERMAINAN TRADISIONAL UNTUK MENSTIMULUS KETERAMPILAN SOSIAL SISWA - Fajar Tri Hatmoko, DWI LESTARININGSIH; Berliana Henu Cahyani; Ana Fitrotun Nisa; LESTARININGSIH, DWI; Henu Cahyani, Berliana; itrotun Nisa, Ana (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
Social development is a very important aspect of child development. Failure to master social skills will make it difficult to adapt to the surrounding environment, which can cause various social problems. One way to develop social skills is to give children enough time to play with peers. Traditional games are a form of stimulation for aspects of social development. The traditional games used are Bakiak and Gobag sodor. This article aims to explain the application of traditional games to stimulate social skills and their implications. This type of research is qualitative descriptive research with 28 grade 1 students as subjects consisting of 18 male students and 10 female students. The research was carried out at SD Negeri Karangnongko I for the 2023/2024 academic year. Data collection techniques in this research are observation, interviews and documentation. The data analysis technique uses Milles and Huberman analysis which consists of data reduction, data presentation and verification. The results of the research that has been carried out show that the application of traditional Javanese games is able to provide a stimulus for social skills in students. These skill aspects are cooperation, adaptation, interaction, self-control, obeying rules, and respecting people.